PROFESSIONAL READING LIST - Harrison, Shawn (Defense AR journal, 2022)
While its subject matter will likely appeal most to life cycle logisticians and engineering and technical management professionals, it will also interest to other Defense Acquisition Workforce members, including DoD program managers, business and financial managers, cost estimators, contracting specialists, and test and evaluation professionals. In addition to a thorough treatment of the 12 DoD Integrated Product Support (IPS) Elements (minus Product Support Management and with some "legacy" terminology), Blanchard addresses reliability and maintainability, availability, functional analysis and requirements allocation, test and evaluation, production, system operational support, modifications, cost estimating, and a variety of related life cycle management topics. [...]readers may find the computer-aided design (CAD) section (which was state-of-the-art at the time of initial publication) a bit rudimentary, but in light of the 2018 DoD Digital Engineering Strategy, Blanchard presciently reminds us the logistician must be able to adapt to rapidly changing design processes, including becoming conversant in, and able to, leverage model viewers and related analytical tools.